(untitled) (Biological Sciences - PJSIR, 2002)
Herbicides incl uding barban , embark, diuron, prometryne , simazine, atrazine, destmetryne, asulam, monuron and linuron are screened for potato sprout suppression activity. A potato sprout suppressant will be expected to inhibit growth of cress root, tomato shoot or potato tissue callus. It is observed that only embark shows pronounced inhibition of callu s growth. Embark was found to be effective as a potato sprout suppressant at high application rate of 500mgkg·1.